Investigation of commonly used assessment methods for predicting fall risk in the elderly (vol 206, 112784, 2025) - Dengiz, Aziz; Aytepe, Ahmet; Sirri, Bayram; Efe, Mehmet (Pergamon-Elsevier Science Ltd, 2026)
[Keywords Not Available]
Keywords: [Keyword Not Available]